2017
DOI: 10.1016/j.vaccine.2016.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Campaigns with oral polio vaccine may lower mortality and create unexpected results

Abstract: Three studies from Guinea-Bissau found conflicting effects of OPV-at-birth (OPV0) on child survival. One study from 2004 suggested excess male mortality among children receiving OPV0 compared with children receiving NoOPV0 during a period of shortage of OPV. However, two subsequent studies showed beneficial effects of OPV0. In 2004, two national OPV-campaigns had been conducted in Guinea-Bissau. In a reanalysis of the 2004-study, in a survival analysis the age-adjusted mortality rate of study participants was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 10 publications
1
23
1
Order By: Relevance
“…The effect of OPV-only campaigns appeared to be slightly stronger for boys than for girls, though the difference was not statistically significant. Other studies of OPV have also suggested a stronger beneficial effect for boys ( 16 , 26 ).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The effect of OPV-only campaigns appeared to be slightly stronger for boys than for girls, though the difference was not statistically significant. Other studies of OPV have also suggested a stronger beneficial effect for boys ( 16 , 26 ).…”
Section: Discussionmentioning
confidence: 87%
“…One observational study has suggested that routine OPV0 compared with NoOPV0 might have a negative effect for boys but not for girls ( 33 ). However, the boys who had “benefited” from not having received OPV0 had been more likely to receive campaign OPV than the boys receiving OPV0 and this is likely to have been the real cause of their lower mortality ( 26 ). In the subsequent RCT to measure the effect, OPV0 was significantly beneficial, particularly for boys ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, several studies have shown OPV-campaigns to be associated with a marked decline in the general mortality rate [45][46][47]. Third, OPV campaigns have modified estimated mortality outcomes in studies of other vaccines [45,48].…”
Section: Example: Oral Polio Vaccinementioning
confidence: 99%
“…Seventh, most studies suggest the OPV has a stronger beneficial effect for boys than for girls [44][45][46].…”
Section: Example: Oral Polio Vaccinementioning
confidence: 99%